Pemertahanan Bahasa Bare’e Pada Masyarakat Pamona di Kecamatan Poso Pesisir: Kajian Sosiolinguistik - Fatmawati Fatmawati; Moh. Tahir; Yunidar Yunidar (Ranah: Jurnal Kajian Bahasa, 2026)
This study discusses the maintenance of the Bare’e language among the Pamona community in Poso Pesisir District from a sociolinguistic perspective. The study focuses on the forms of Bare’e language maintenance and the factors influencing the continuity of its use amid social changes within the community. The objectives of this study are to describe the forms of Bare’e language maintenance among the Pamona people in Poso Pesisir District and to analyze the factors affecting the sustainability of the language’s use. This research employed a qualitative method with a sociolinguistic approach. The data were collected through observation, in-depth interviews, and documentation involving traditional leaders, teachers, parents, young people, and members of the Pamona community as speakers of the Bare’e language. Data analysis applied the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing. The findings reveal that the maintenance of the Bare’e language still exists in both formal and informal domains. In formal settings, the Bare’e language is used in schools, village institutions, and traditional ceremonies as a symbol of cultural identity and a medium for conveying the social values of the Pamona community. In informal settings, the language is used within families, daily social interactions, and local cultural activities. The factors influencing the continuity of the Bare’e language consist of internal and external factors. Internal factors include community awareness of the importance of the local language, language attitudes, and the role of families and traditional leaders in language transmission. External factors include the dominance of the Indonesian language in formal education, the influence of globalization and digital media, urbanization, and the support of social institutions and the government for local language preservation. This study demonstrates that maintaining the Bare’e language requires the active involvement of the community, families, and social institutions to ensure that the Bare’e language continues to survive as a cultural identity of the Pamona people in Poso Pesisir District. Abstrak Penelitian ini membahas pemertahanan bahasa Bare’e pada masyarakat Pamona di Kecamatan Poso Pesisir dalam kajian sosiolinguistik. Permasalahan dalam penelitian ini difokuskan pada bentuk pemertahanan bahasa Bare’e serta faktor-faktor yang memengaruhi keberlangsungan penggunaannya di tengah perubahan sosial masyarakat. Penelitian ini bertujuan untuk mendeskripsikan bentuk pemertahanan bahasa Bare’e pada masyarakat Pamona di Kecamatan Poso Pesisir dan menganalisis faktor-faktor yang memengaruhi keberlangsungan penggunaan bahasa tersebut. Penelitian menggunakan metode kualitatif dengan pendekatan sosiolinguistik. Data diperoleh melalui observasi, wawancara mendalam, dan dokumentasi terhadap tokoh adat, guru, orang tua, generasi muda, dan masyarakat Pamona sebagai penutur bahasa Bare’e. Analisis data menggunakan model Miles dan Huberman yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa pemertahanan bahasa Bare’e masih berlangsung dalam ranah formal dan informal. Dalam ranah formal, bahasa Bare’e digunakan di sekolah, instansi desa, dan kegiatan adat sebagai simbol identitas budaya dan media penyampaian nilai sosial masyarakat Pamona. Dalam ranah informal, bahasa Bare’e digunakan dalam lingkungan keluarga, interaksi sosial masyarakat, dan kegiatan budaya lokal. Faktor-faktor yang memengaruhi keberlangsungan penggunaan bahasa Bare’e terdiri atas faktor internal dan faktor eksternal. Faktor internal meliputi kesadaran masyarakat terhadap pentingnya bahasa daerah, sikap bahasa, serta peran keluarga dan tokoh adat dalam pewarisan bahasa. Faktor eksternal meliputi dominasi Bahasa Indonesia dalam pendidikan formal, pengaruh globalisasi dan media digital, urbanisasi, serta dukungan lembaga sosial dan pemerintah terhadap pelestarian bahasa daerah. Penelitian ini menunjukkan bahwa pemertahanan bahasa Bare’e memerlukan keterlibatan aktif masyarakat, keluarga, dan lembaga sosial agar bahasa Bare’e tetap bertahan sebagai identitas budaya masyarakat Pamona di Kecamatan Poso Pesisir.